Education in The Islam Nusantara Perspectives - Dimas Indianto S; Intan Nur Azizah; Sunhaji Sunhaji; Nurfuadi Nurfuadi (Universitas Sebelas Maret, 2022)
This study aims to introduce the concept of Islamic learning with a distinctive archipelagic personality, as a conceptual proposition for the growth of today's citizens. This is a logical consequence of the meaningful position of learning as a forum for the regeneration of citizens. This research is a literature research. Data collection techniques by reviewing the literature related to the research theme. Furthermore, the data found will be reduced according to the research theme for further conclusions drawn. This study provides an understanding that the development of Islam Nusantara cannot be separated from Nusantara Islamic Education. From the birth of Islam in the archipelago, Islamic education has positioned itself as an important part of education, but it is still in a simple and very local environment. Over time, Islamic education in the archipelago has experienced a shift, progress, change and innovation which of course continues to grow today.